Stochastic modeling in broadband communications systems - Kaj, Ingemar (Society for Industrial and Applied Mathematics, 2002)
Annotation Mathematical methods based on the theory of stochastic processes have long been used effectively in telephone traffic modeling. Today's modern network traffic, which is distinctly different from traditional voice traffic, generates challenging mathematical and statistical problems. Stochastic Modeling in Broadband Communications Systems provides a concise overview of stochastic models and mathematical techniques for solving these problems and enhances readers' overall understanding of communication systems. The book also presents an excellent introduction, particularly for students and professionals in probability and applied mathematics, to a huge area of interesting problems and models arising from modern developments in broadband channel transmission systems.
Keywords: Broadband communication systems -- Mathematical models.; Stochastic analysis.; elektronické knihy; electronic books